Male and female Anolis carolinensis maintain their dimorphism despite the presence of novel interspecific competition. (25th September 2021) - Stuart, Yoel E.; Sherwin, J. William; Kamath, Ambika; Veen, Thor
Abstract: Natural selection favors sexual dimorphism that reduces resource competition between the sexes of the same species. However, niche partitioning among interspecific competitors should counter such divergence, as partitioning the niche results in smaller total niche widths for each individual species, leaving less room for the sexes to diverge. A straightforward (and long‐standing) hypothesis emerges: species in competitor‐rich ecological communities should show less sexual dimorphism than species in competitor‐poor ecological communities. Here, we test this prediction using a well‐documented natural experiment generated by the recent arrival of Anolis sagrei to a set of small islands in Mosquito Lagoon, Florida, containing Anolis carolinensis . Despite known interspecific habitat partitioning and rapid evolution in habitat‐use traits by A. carolinensis in this system, sexual dimorphism between male and female A. carolinensis was not reduced as predicted on two‐species islands relative to islands with only A. carolinensis . This is consistent with a small but growing body of empirical tests of the dimorphism–richness hypothesis that have been ambiguous in their support at best. A rethinking of the validity of this intuitive hypothesis is needed.